2021
DOI: 10.1136/bmjopen-2021-049011
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for pre-exposure prophylaxis (PrEP) among men who have sex with men and transgender women at risk of HIV infection: a multicentre protocol for a discrete choice experiment in Brazil

Abstract: IntroductionPre-exposure prophylaxis (PrEP) is an important and well-established prevention strategy for sexual acquisition of HIV. In Brazil, transgender women (TGW) and men who have sex with men (MSM) bear the largest burden among key populations. Little is known about preferences for PrEP characteristics in these vulnerable populations in Latin America. The goal of this study is to investigate preferences of TGW and MSM with respect to PrEP characteristics, whether current user or not, and to assess any att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Here we describe the design and methods from our ongoing DCE to assess user preferences for PrEP delivery from an online pharmacy in Kenya. This study adds to the small but growing literature of DCE protocols for HIV prevention [24][25][26][27][28] and additionally provides detailed information on DCE attribute selection and refinement, materials used for staff training and methods for participant recruitment. The methods described along with slide decks of training materials and survey guides can assist other researchers interested in designing DCEs for HIV prevention.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Here we describe the design and methods from our ongoing DCE to assess user preferences for PrEP delivery from an online pharmacy in Kenya. This study adds to the small but growing literature of DCE protocols for HIV prevention [24][25][26][27][28] and additionally provides detailed information on DCE attribute selection and refinement, materials used for staff training and methods for participant recruitment. The methods described along with slide decks of training materials and survey guides can assist other researchers interested in designing DCEs for HIV prevention.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…23,[36][37][38] In descriptive choice experiment (DCE) studies conducted among sexual and gender minorities in Brazil and Peru during 2020-2021, long-acting presentations and frequency of taking PrEP were important attributes in choosing PrEP modality. 20,21,39 Our findings provide additional information about preferences for alternative modalities to oral PrEP such as injectable PrEP among MSM in Latin America.…”
Section: Discussionmentioning
confidence: 79%
“…We expect the acceptability of CAB-LA in Brazil to be high. Data from a web-based survey and descriptive choice experiment have shown that injectable PrEP was preferred over other PrEP modalities in Brazil [ 35 - 37 ]. Our results regarding PrEP choice among individuals seeking PrEP in health units will increase this body of evidence.…”
Section: Discussionmentioning
confidence: 99%